Formation of the sound-syllabic structure of primary school pupils’ speech with intellectual disabilities in Ukrainian language lessons - V. Mykhailenko (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The purpose of the study was to determine the impact of various methods and techniques on the development of language skills in children with intellectual disabilities. Particular attention was paid to the analysis of innovative approaches, such as mobile applications and interactive teaching methods used to improve oral skills in an inclusive educational environment. The study confirmed the effectiveness of alternative methods and techniques for correcting language deficiencies in students with intellectual disabilities. Children who regularly used interactive tools showed better results in the development of phonemic awareness and the ability to distinguish sounds. Interactive exercises helped alleviate problems with word articulation and syllabic structure development. Studies have shown that children with intellectual disabilities have difficulty perceiving and analysing sounds, and this is due to a lower level of phonemic awareness. The process of forming phonemic awareness is so important in the early stages of speech development that its disruption affects the further acquisition of syllable structure. The article describes approaches to the diagnosis and correction of these disorders, including special exercises for the development of phonemic awareness, articulation exercises and teaching methods for the correction of disorders of the structure of speech sounds and their constituent components. The results can be used to improve educational programmes in specialised schools for children with intellectual disabilities. This contributes not only to the development of language skills, but also to the overall improvement of students' communication skills. The introduction of innovative methods into the educational process provides better results of correctional activities and creates a more favourable environment for children with special needs